MEASUREMENT OF IRON, MANGANESE, COPPER, COBALT AND LEAD TO ASSESS THE EDIBLE FITNESS OF M. CEPHALUS COLLECTED FROM LASBELA (BALOCHISTAN), PAKISTAN, USING ATOMIC ABSORPTION SPECTROSCOPY - Afzal, Fehmeeda; ullah, Sami; Nadeem, Ashraf; Aslam, Muhammad; Shafi, Muhammad; Hasni, Khalil; Hakeem, Abdul; Tariq, Sonia (Malaysian Journal of Science, 2022)
The sea serves as a good source of food. The direct discharge of pollutants into aquatic environments can result in exceeded levels of heavy metals. This can harm the organisms and cause serious health issues when consumed by humans. Mugil cephalus is consumed as food, and its continuous analysis for heavy metals is required for food safety. Some selected metals – namely iron, copper, manganese, cobalt and lead – were evaluated in muscle tissues of Mugil cephalus collected from two major fish landing sites (i.e. Gaddani and Damb) along the Lasbela coast of Balochistan). The concentration of metals was determined using an atomic absorption spectrometer. For this purpose, several digestion methods were used to digest the meat for comparison. Using H2SO4, HNO3 and HClO4 was the most effective method, which is an important analytical finding for future researchers to consider. The concentrations of metals assumed the order of Fe > Cu > Pb > Mn > Co in samples from Gaddani and Fe > Cu > Mn > Pb > Co in samples taken from Damb. Among the metals analyzed, iron levels at Gaddani and Damb were found within the permissible values suggested by the World Health Organization (WHO), Food and Agriculture Organization (FAO), and United States Environmental Protection Agency (USEPA). Copper and lead levels were higher than the safe limits in samples from both sites. The estimated daily and weekly metals intake in an average 70 kg person were lower than the limits proposed by the FAO and WHO for all metals. The overall results revealed that the selected fish species is safe for consumption and presents no hazardous effects on human health. However, Gaddani fish Harbor and Damb should be protected from the direct discharge of pollutants, and the future monitoring of M. cephalus fish is required to make sure the edible meat is safe for consumption.